Editorial Vol4 no2 - Sandy Cameron (Scottish Journal of Residential Child Care)
For ten years now, I have had the privilege of chairing the management committees of both the Centre for Residential Child Care and then the Scottish Institute for Residential Child Care (SIRCC). As I look back over the years I think Scotland can be proud of what it has set out to do in creating better services for our young people. The commitment by government to invest in setting up a unique institute in the form of SIRCC sent out a clear signal that residential child care has an enduring and important place on the spectrum of services for those children and young people who need and will continue to need public care. The very presence of this journal is evidence of the opportunity that has been taken to improve the understanding and knowledge that must underpin our services.